Introduction to UAV systems - Fahlstrom, Paul Gerin; Gleason, Thomas J.; Sadraey, Mohammad H. (Hoboken, NJ : Wiley, 2022)
"Now in an updated Fifth Edition, Introduction to UAV Systems, provides a broad foundation on all aspects of Unmanned Aerial Vehicles (UAV) and Unmanned Aerial Systems (UAS). This thoroughly revised edition introduces the history, classes, and missions of UAVs, then introduces readers to key UAV topics such as aerodynamics, stability and control, propulsion, loads and structures, mission planning, payloads, and communication systems. New material is introduced to cover topics like quadcopters, navigation systems, and ground control stations and new examples highlight the latest industry technologies. The book is an ideal introduction to the world of UAV Systems for both professionals and students, with new end-of-chapter review questions to help enhance reader comprehension and support university courses such as Unmanned Aircraft Systems Design, Introduction to Unmanned Aerial Systems, and Unmanned Aircraft System Operations."--
Includes bibliographical references and index.
Keywords: Drone aircraft; Cruise missiles